Comparative analysis of cultural and psychological differences in the personalities of modern adolescents - Mursalyeva, Giultakin; Mishina, Marina Mihailovna (Психолог, 2025)
The question of ethnic identity remains relevant for the research community. Contemporary studies focus on examining the ethnic identity of individuals, as well as identifying cultural and psychological differences and changes in identity throughout a person's life. This article presents the results of an empirical study on the structure of ethnic identity among adolescents from Moscow, Stavropol (Russia), and Ismailly (Azerbaijan). The subject of the study is the cultural and psychological differences in the structure of ethnic identity among modern adolescents included in different social environments. The aim of the article is to theoretically substantiate and empirically reveal the cultural and psychological differences in the structure of ethnic identity among contemporary adolescents living in different regions of Russia and in Azerbaijan. The object of the study is the structure of personal ethnic identity. Research methods: theoretical analysis, observation, formative experiment, psychodiagnostic methods and questionnaires, mathematical methods: two-way analysis of variance, Student's t-tests, Pearson's chi-square test. The empirical base of the research includes 295 adolescents (students in grades 6-8): 121 adolescents from Moscow, 45 adolescents from Stavropol, and 129 adolescents from Ismailly. The significant scientific novelty of this study lies in determining the cultural differences in the structure of personal ethnic identity as influenced by the cultural environment, identifying both common (characteristic of all groups) and specific (characteristic of a particular group) relationships. Conclusions: It has been confirmed that the cultural environment surrounding an adolescent significantly influences the indicators of personal ethnic identity: among adolescents from the ethnically diverse environments of Moscow and Stavropol, a positive type of ethnic identity predominates, which is substantively reflected in the behavioral component. Among adolescents from Ismailly, there is a pronounced ethno-egoism, ethno-isolationism, and ethno-fanaticism, alongside a confirmed high level of anxiety and social distancing, which also relate to the indicators of the behavioral component. The level of suspicion among adolescents from Ismailly, as manifested in the behavioral component of personal ethnic identity, is significantly higher than that of adolescents from the cultural environments of Moscow and Stavropol. The area of application of the research results: possible for the development of educational and social programs aimed at fostering constructive interethnic interaction.